MAQASHID SHARIAH MUZAKKI'S REVIEW USING THE LATEST SEVEN DIMENSIONS - Faisal, Yusuf; Etty Murwaningsari; Tatik Mariyanti (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study has a novelty on the variables of maqashid shariah. Where the maqashid sharia variable in this study uses seven dimensions which previously used five dimensions. The dimension of novelty is tested to see its effect on the decision of the muzakki to issue zakat. This test was conducted with a sample of 423 muzakki throughout Indonesia. The results of this study found that the newness of the dimensions in the maqashid sharia variables, namely protecting the environment and maintaining security, became a consideration for muzakki in issuing zakat